2015
DOI: 10.1007/s00167-015-3923-y
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis: a comparison of an all-polyethylene tibial implant and its metal-backed equivalent

Abstract: Purpose: The hypothesis of this study is that all-polyethylene (APE) tibial impalnts offer a biomechanical profile similar to metal backed tray (MBT). There are significant financial cost saving implications, in selected patient groups, if APE performs as well MBT. Methods: Using a finite element analysis (FEA) of CAD models provided by DePuy (Leeds), stress distributions were investigated for both an APE and MBT tibial implant. The performance was assessed for cancellous bone at 700MPa (normal) and at 350MPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Thompson et al found that higher stress shielding (resorption) occurred around the keel and stem of the MBT, which revealed greater potential for bone loss in these areas. The APT implant had no areas of bone resorption (increased flexible resulted in less stress shielding) [17]. A similar outcome was also found by Scott et al, who reported that significant stress shielding is found in MBT cases, while increased bone density was found in APT cases, particularly in the bones immediately beneath the baseplate.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Thompson et al found that higher stress shielding (resorption) occurred around the keel and stem of the MBT, which revealed greater potential for bone loss in these areas. The APT implant had no areas of bone resorption (increased flexible resulted in less stress shielding) [17]. A similar outcome was also found by Scott et al, who reported that significant stress shielding is found in MBT cases, while increased bone density was found in APT cases, particularly in the bones immediately beneath the baseplate.…”
Section: Discussionsupporting
confidence: 55%
“…However, although the polyethylene prosthetic bone cement was generally in a high stress state, this was lower than its fatigue endurance limit [15]. Cement stress in other studies also reported increased compressive stress at the cement–cancellous bone interface for the APT implant [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While bone cement provides for stable fixation between the trabecular bone and implant, it also results in stress-shielding of the bone that is interdigitated with cement (Zhang, Cossey et al 2016). Trabecular bone distal to metal-backed tibial trays has been shown to be more stress shielded than all-polyethylene implants using computational modeling (Thompson, Yohuno et al 2015). Changes in peri-prosthetic tibial bone density may not always lead to complications, with good clinical outcomes achievable (Jaroma, Soininvaara et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In previous FEA studies, cancellous bone stresses were examined to assess its mechanical performance. However, it has been demonstrated that bone is a highly heterogeneous material and stress itself does not have a strong meaning if it is not related to its strength, i.e., yield stress, which has been shown to be correlated to bone density (Completo et al, 2008; 360 MMMS 16,2 Perillo-Marcone et al, 2003;Thompson et al, 2016). Nonetheless, it has also been demonstrated, by means of an experimental study, that the von Mises criterion is not accurate in assessing cancellous bone performance.…”
Section: Introductionmentioning
confidence: 99%